A Proof of Concept on Enhancing Virtual Museum Experience Through Real-time Audio Communication - Araújo, Calíope Corrêa de; Teixeira, João Marcelo Xavier Natário (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2023: Anais do XX Congresso Latino-Americano de Software Livre e Tecnologias Abertas, 2023)
By introducing the possibility of communication within a virtual environment, it is possible to improve visitor interaction and increase immersion through the feeling of presence, a fundamental concept within Virtual Reality. This work therefore proposes an innovative solution to the problem of lack of interaction between visitors during a virtual tour using open source software resources. Making use of the A-Frame framework, together with Networked A-Frame, a proof of concept was implemented with the aim of showing that it is possible to improve the experience of a virtual visit to the museum, enabling visitors to communicate in a very similar way to what would happen in a real visit, in a physical space. A brief case study was carried out based on the creation of an alternative virtual tour, modifying the existing virtual tour of the Cais do Sertão Museum, in Pernambuco, with the proposed solution. This paper will explore the paths used to build the proof of concept, as well as the results obtained and possibilities for future work, in addition to presenting possible scenarios for applying the proposed solution seeking to improve immersive experiences in virtual tours of museums.